Prednisone Therapy for Duchenne Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The effects of prednisone on muscle function and the extent of steroid-related adverse effects were studied in 17 ambulant children with Duchenne muscular dystrophy (DMD) at University Hospital, Groningen; Rehabilitation Centre, Utrecht; and Leiden University Medical Centre, the Netherlands.